Health Promoting Hospitals – Assessing developments in the network (Italian Journal of Public Health, 2007)
Hospitals are specific organizational settings for health promotion efforts. As health care institutions they are already oriented at health, or better at ill health, but with a rather limited focus on health outcomes for patients. Therefore, the Ottawa Charter explicitly asks for the reorientation of health services. And, hospitals also have considerable health effects for other stakeholder populations. This specific potential and challenge has been taken up by the WHO network of Health Promoting Hospitals (HPH), in the last two decades. Based on available literature the article relates the HPH concept to a more general paradigm of health promoting organizational settings; reconstructs the developmental phases of the international WHO HPH Network; elaborates on its concept development and implementation experiences, and discusses its rather limited investments in evaluation studies and the few assessments from outside. HPH has developed a convincing comprehensive concept by demonstration projects, using systematically action and evaluation research. To a lesser degree, the same holds true for its developments of health promotion policies for selected vulnerable groups and linking HPH to quality methodology. But there is no systematic evaluation of health promotion in and by hospitals, especially for the networks and member hospitals of HPH. Even if much of the relevant evidence for HPH comes and will have to come from more general clinical epidemiological, health promotion, quality, organizational and management research, there is need for specific HPH evaluation research, to better utilize, what can be learned from the social experiment of HPH.
Keywords: hospitals; health promotion; settings approach